Pengaruh Asset Growth, Leverage, dan Efisiensi Operasional Terhadap Nilai Perusahaan pada Perusahaan Sektor Transportasi Dan Logistik di Bursa Efek Indonesia (BEI) Periode 2022-2025 - Rorelysia Putri Noverdiana; Hestin Sri Widiawati; Faisol (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the discrepancies found in previous research results regarding the influence of asset growth, leverage, and operational efficiency on company value, particularly in the transportation and logistics sector. This study aims to analyze the influence of asset growth, leverage, and operational efficiency on the value of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2025 period. The approach used is quantitative with a causal research type. The research data consists of secondary data obtained from the annual financial reports of transportation and logistics companies listed on the IDX. The sampling technique used a purposive sampling method, resulting in 12 companies with an observation period of four years, resulting in a total of 48 observations. Data analysis was performed using panel data regression with a Random Effects Model using STATA software version 14. The results show that asset growth and leverage have no significant effect on company value, while operational efficiency has a significant effect on company value. Simultaneously, asset growth, leverage, and operational efficiency have a significant effect on company value. These findings indicate that operational efficiency is an important factor in increasing company value and can be a consideration for investors in assessing the performance of transportation and logistics companies.